Family Maldanidae - A guide to species in waters around the British Isles - Garwood, P. R. (NMBAQC 2006 taxonomic workshop, Dove Marine Laboratory, 2007)
[none]
World Polychaeta Database (WPolyDb). Link valid 2015-07-24